2017
DOI: 10.1371/journal.pone.0186083
|View full text |Cite
|
Sign up to set email alerts
|

Heat stress induces expression of HSP genes in genetically divergent chickens

Abstract: BackgroundChickens are animals that are sensitive to thermal stress, which may decrease their production level in terms that it affects feed intake and thus, decreasing body weight gain. The Heat Shock Factors (HSF) and Heat Shock Proteins (HSP) genes are involved in the key cellular defense mechanisms during exposure in hot environments. Aimed with this study to analyze the expression of HSF1, HSF3, HSP70 and HSP90 genes in two local breeds (Peloco and Caneluda) and a commercial broiler line (Cobb 500®) to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 48 publications
5
50
0
1
Order By: Relevance
“…In contrast, some limitations of the present study include the relatively small sample size and the fact that the effect of TM on embryonic mortality and physiological parameters was not fully explored. However, the sample sizes utilized in the current study are in line with previously published reports [12,29].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In contrast, some limitations of the present study include the relatively small sample size and the fact that the effect of TM on embryonic mortality and physiological parameters was not fully explored. However, the sample sizes utilized in the current study are in line with previously published reports [12,29].…”
Section: Discussionsupporting
confidence: 68%
“…Our findings show that CS decreased hepatic and splenic Hsp70 expression, respectively. Previous reports have shown that, during HS, Hsp70 expression was found to be lower in a commercial broiler breed (Cobb) compared to local ones (Caneluda and Peloco), and this high expression level was associated with resistance to elevated temperatures in the local breeds [12]. Moreover, Cobb and Hubbard chicks subjected to TM were found to express higher cardiac, hepatic, muscular and splenic levels of Hsp70 during post-hatch heat challenge [13,34,35,42].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Responses to heat vastly depend on the genetic adaptation of the individual [16] but also on environmental factors, such as intestinal microbiota [17]. Compromised genetic or environmental conditions result in poorer thermoregulation [18].…”
Section: Introductionmentioning
confidence: 99%
“…Among HSPs, HSP70 is most closely associated with cytoprotection and cellular thermoregulation (Beckham et al, 2008;Craig & Gross, 1991). Heat conditions increased the expression of HSP70 in a time-dependent manner in broilers (Yu & Bao, 2008) and native chickens (Cedraz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%